2018
DOI: 10.1002/cphc.201800507
|View full text |Cite
|
Sign up to set email alerts
|

UV Photoionization of Sodium‐Doped Formic Acid Clusters

Abstract: The processes involved in the photoionization of sodium-doped clusters are complex, not fully understood for many systems and still strongly debated, especially because of the discrepancy between experimental results and predicted cluster structures. We have performed a study on sodium doped formic acid clusters based on UV photoionization spectroscopy and DFT/TDDFT calculations. Apart from the monomer, all the predicted structures show vertical ionization potential values higher than those obtained by the pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 55 publications
(76 reference statements)
0
10
0
Order By: Relevance
“…In the supersonic expansion in the vacuum, carboxylic acid vapors easily aggregate forming pure acid or mixed acid‐water clusters detected in our apparatus as Na‐doped clusters by laser UV ionization [13–15] . In particular, in ref [14] we demonstrated that the ion signals of Na−(FA) n are produced by one‐photon ionization, so the cluster ionization potentials were correctly assigned in the laser UV range.…”
Section: Resultsmentioning
confidence: 56%
See 4 more Smart Citations
“…In the supersonic expansion in the vacuum, carboxylic acid vapors easily aggregate forming pure acid or mixed acid‐water clusters detected in our apparatus as Na‐doped clusters by laser UV ionization [13–15] . In particular, in ref [14] we demonstrated that the ion signals of Na−(FA) n are produced by one‐photon ionization, so the cluster ionization potentials were correctly assigned in the laser UV range.…”
Section: Resultsmentioning
confidence: 56%
“…We have already found appearance energies in the UV range for similar classes of clusters. These appearance energies have been attributed to clusters characterized by adiabatic ionization energies in the same UV energy range of the PIE spectra [14] . In fact, the adiabatic photoionization implies a significant rearrangement of the ionic core and formation of electronic Rydberg‐type excited states that could give rise to autoionization during orbital relaxing.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations